Random amplified polymorphic DNA-PCR and ERIC PCR analysis on Vibrio parahaemolyticus isolated from cockles in Padang, Indonesia - Yusop, Zulkifli; Mohamed Alitheen, Noorjahan Banu; Radu, Son; Abdul Rahim, Raha; Lihan, Samuel; Yeap, Swee Keong; Nishibuchi, Mitsuaki (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
In this study, RAPD-PCR and ERIC-PCR were used to study the epidemiology of V. parahaemolyticus isolated from cockles in Padang, Indonesia. The Gold Oligo OPAR3 primer produced bands ranged from 1-8 with sizes from 0.2 – 5.0 kb and the Gold Oligo OPAR8 primer produced 1-7 bands with sizes 0.7 – 1.5 kb. Both primers produced twenty five RAPD patterns with a few isolates failed to produce any products. Based on phylogenetic dendrogram, all the isolates can be divided into 6 major clusters with similarity between 0 to 52%. For the ERIC primer, it produced bands ranged from 3-15 with sizes from 0.1 – 5.0 kb and twenty seven different ERIC patterns. Construction of the phylogenetic dendogram showed the isolates can be divided into 4 major clusters with similarity between 56 to 86%. The high diversity of both processes may be due to the multiple contamination sources of V. parahaemolyticus.